2007
DOI: 10.1038/sj.ijir.3901618
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of changing testosterone gel preparations (Androgel or Testim) among suboptimally responsive hypogonadal men

Abstract: The study objective was to evaluate the efficacy of changing testosterone gel preparations among suboptimally responsive hypogonadal men. The records of all hypogonadal men on gel (Testim or Androgel) testosterone replacement therapy (TRT) were reviewed to identify men who underwent a brand substitution in gel TRT due to initial suboptimal response. Total and free serum testosterone levels and the presence of hypogonadal symptoms (ADAM) were compared pre-and post-gel substitution. Of the 370 hypogonadal men on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…However, in contrast to findings in younger hypogonadal men, the protective effects of TRT in older men have been equivocal [813]. For example, 20–28% of aging men experience either no response or a negative adverse event in response to TRT [10, 14]. Importantly, these adverse effects of TRT appear to be concentration dependent, with serious adverse effects observed in 28% of aging men with testosterone levels >10 ng/ml, 23% of aging men with 5–10 ng/ml total testosterone, and 15% of aging men with testosterone <5 ng/ml [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to findings in younger hypogonadal men, the protective effects of TRT in older men have been equivocal [813]. For example, 20–28% of aging men experience either no response or a negative adverse event in response to TRT [10, 14]. Importantly, these adverse effects of TRT appear to be concentration dependent, with serious adverse effects observed in 28% of aging men with testosterone levels >10 ng/ml, 23% of aging men with 5–10 ng/ml total testosterone, and 15% of aging men with testosterone <5 ng/ml [15].…”
Section: Introductionmentioning
confidence: 99%
“…28 Other studies of Testim ® use of 3 to 12 months' duration reported comparable increases in TT levels. 27,46,47 Data on changes in TT and FT levels in men with HIV/ AIDS treated with topical testosterone gels are scarce. One prospective, randomized, open-label study of 48 men with HIV who had not responded to AndroGel ® therapy reported significant improvements in sexual drive and satisfaction, erectile function, and problem assessment in men treated with Testim ® for 4 weeks compared with the group that continued using AndroGel ® ; however, no pharmacokinetic data were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although from the clinical point of view, these differences are relatively small, the statistical determination of bioequivalence using 90% CIs indicated that the differences in C max and AUC 0-24h v alues observed between these two preparations were sufficient to suggest that these preparations are not bioequivalent [55,56]. Following this, Grober et al observed in 370 T-gel-treated hypogonadal men that changes in the specific gel preparation among initially unresponsive hypogonadal men is justified prior to abandoning or considering more invasive T therapy [57]. In this study, more men changed from AndroGel to Testim use than from Testim to AndroGel use.…”
Section: Review -Lunenfeld and Oettelmentioning
confidence: 99%